A new genus of Conopidae from Europe (Diptera) - Stuke, Jens-Hermann (Zootaxa, 2014)
The monotypic genus Merziella gen. nov. (Palaearctic Region: Europe) is described. A key to the genera of the subfamily Myopinae is presented.